Large-Eddy Simulation of a Jet-in-Hot-Coflow Burner Operating in the Oxygen-Diluted Combustion Regime - Ihme, Matthias; Zhang, Jian; He, Guowei; Dally, Bassam (Flow, turbulence and combustion, 2012)
Large-eddy simulations of moderate and intense low-oxygen dilution (MILD) combustion of a jet-in-hot-coflow (JHC) burner are performed. This burner configuration consists of three streams, providing fuel, oxygen-diluted coflow, and air to the burner. To account for the mixing between the three reactant streams, a three-stream flamelet/progress variable (FPV) formulation is utilized. This model was previously applied to a condition corresponding to the upper range of MILD-combustion, and the objective of this contribution is to further investigate this model in application to highly diluted operating conditions. Comparisons of mean and conditional results show that the model accurately captures effects of increasing oxygen-depletion on the flame-structure and heat-release, and predictions for temperature and species mass fractions are in overall good agreement with experiments.